A Model of Imam's Leadership and Mosque Performance in Malaysia - Mahazan Abdul Mutalib @ Talib; Abdullah, AG (Univ Sultan Azlan Shah, 2024)
This article aims to discuss three major arguments. First, mosque performance could be measured at least by using two dimensions; number of regular jamaah (congregants) of the mosque and number of religious classes organized by the mosque. Second, the association of imams' leadership and mosque performance is centralized on the issue of how imams' leadership traits influence their effective leadership behavior capacity in predicting their performance as mosque leaders. Third, the association of imams leadership traits, leadership behavior, and mosque performance could be moderated by the level of autonomy the imams' have. This study applies content analysis approach to analyze researches and theories in organizational leadership field of study as well as mosque performance. Based on the analysis conducted, this study proposes a model of imams' leadership and mosque performance association to be applied in researches concerning imams' leadership and mosque performance in Malaysia or elsewhere.